2011
DOI: 10.1039/c1an15570a
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of a novel cyclodextrin derivative of benzimido-β-cyclodextrin and its enantioseparation performance in HPLC

Abstract: A novel cyclodextrin (CD) derivative, mono-6-deoxy-benzimide-β-CD (MB-β-CD), in which a rigid substituent was linked to the narrow edge of the CD with a flexible H(2)C-N group, was successfully synthesized through the condensation of mono-6-deoxy-6-amino-β-cyclodextrin and benzaldehyde. To evaluate its enantioseparation abilities and investigate the role of the CD substituents and linkage in chiral recognition, MB-β-CD and mono-6-deoxyphenylimine-β-CD (MP-β-CD) with a rigid linkage were compared in the separat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
(25 reference statements)
0
12
0
Order By: Relevance
“…Comparison with CCN-CSP and CCP-CSP 20 21 12 , CCC3M4-CSP afforded much higher resolution for aryl alcohols. Impressively, the R s of ( E )-1,3-diphenylprop-2-en-1-ol was as high as 13.7, which was over 3 and 11 times higher than that obtained with mono-6-deoxyphenylimine-β-CD and mono-6-deoxybenzimide-β-CD, respectively 31 . These behavious can be explained with the enhanced π-π conjugation between C=C bond and phenyl group via forming stronger π–π interactions, dipole-dipole and steric repulsion interactions with the existence of 3-chloro and 4-methyl in phenylcarbamate moieties.…”
Section: Resultsmentioning
confidence: 73%
“…Comparison with CCN-CSP and CCP-CSP 20 21 12 , CCC3M4-CSP afforded much higher resolution for aryl alcohols. Impressively, the R s of ( E )-1,3-diphenylprop-2-en-1-ol was as high as 13.7, which was over 3 and 11 times higher than that obtained with mono-6-deoxyphenylimine-β-CD and mono-6-deoxybenzimide-β-CD, respectively 31 . These behavious can be explained with the enhanced π-π conjugation between C=C bond and phenyl group via forming stronger π–π interactions, dipole-dipole and steric repulsion interactions with the existence of 3-chloro and 4-methyl in phenylcarbamate moieties.…”
Section: Resultsmentioning
confidence: 73%
“…In our previous work, we confirmed that the rigid C=N bonds attached to CDs are essential for obtaining good enantioselectivity in asymmetric catalysis [12][13][14]. This configuration may have a tendency toward hydrolysis, which could affect the stability of chiral stationary phases.…”
Section: Introductionmentioning
confidence: 65%
“…Three ferrocene derivatives were examined in this paper (Table 1, entries [14][15][16]. The corresponding graph is given in Fig.…”
Section: The Polar-organic Phase Modementioning
confidence: 99%
“…Most of selected analytes could be well resolved (R s > 1.5) under reversed-phase mode for both CSPs. Also, mono-6-deoxy-benzimide-β-CD was synthesized via the condensation of mono-6-deoxy-6-amino-β-CD and benzaldehyde [47]. The chiral recognition ability of CD substituents and linkage was further investigated in HPLC towards 36 chiral compounds.…”
Section: Monocationic Cd-derived Chiral Stationary Phasesmentioning
confidence: 99%